Pengaruh pemberian jelly mengandung glukomanan porang (Amorphophalus oncophyllus) dan inulin sebagai makanan selingan terhadap berat badan, IMT, lemak tubuh, kadar kolesterol total, dan trigliserida pada orang dewasa obesitas - Rissa Saputri; Rizka Qurrota A’yun; Emy Huriyati; Lily Arsanti Lestari; Sri Rahayoe; Yusmiati Yusmiati; Okta Haksaica Sulistyo; Eni Harmayani (Jurnal Gizi Klinik Indonesia, 2021)
Effect of jelly containing of porang (Amorphophalus oncophyllus) glucomannan and inulin as a snack to the body weight, BMI, body fat, total cholesterol, and triglyceride levels in obese adultBackground: Obesity is a major risk factor for noncommunicable diseases, especially cardiovascular disease. Porang glucomannan and inulin are water-soluble fibers that have been widely studied for their health benefits. Jelly products that contain both types of fiber are expected to have the ability to support the diet program in adults with obese nutritional status. Objective: To determine the effect of giving jelly containing a combination of glucomannan porang and inulin on body weight, BMI, body fat, total cholesterol, and triglyceride levels in obese adults.Methods: This research is a randomized controlled trial using a pre and post-test design. A total of 55 subjects who live in the Special Region of Yogyakarta, participated in the study until the end of 8 weeks. Subjects were divided into 3 groups; 18 people in the group who were given jelly containing glucomannan porang and inulin (porang-inulin jelly group), 17 people in the group who were given placebo jelly (placebo jelly group), and 20 people in the negative control group who did not get jelly (negative control group). All subjects received a low-calorie diet intervention of 1,500 kcal in the first month and 1,200 kcal in the second month. Results: There was a significant reduction in body weight and BMI (p<0.05) in all groups, but there was no difference in the effect between the porang–inulin jelly group and the other groups (p>0.05). Clinically, there was a significant decrease in body fat percentage in the porang-inulin jelly group, in subjects with the category of an excess fat percent (-0.90 ± 0.49%) and obesity (-1.48 ± 0.83%). A significant decrease in fat percentage also occurred in the porang-inulin jelly group, both in male subjects (-1.42 ± 0.50%) and female (-1.15 ± 0.82%), while in the placebo jelly group and negative control, the decrease did not occur in all categories and genders. There was an increase in total cholesterol levels in the negative control group (p<0.05) after the study (+7.45 ± 13.18 mg/dL). In the porang-inulin jelly group, the increase in cholesterol levels did not occur significantly either in general or based on clinical categories and gender. Conclusion: Consumption of porang-inulin jelly may support weight loss programs, BMI, percent body fat, and inhibit the increase of total cholesterol and triglyceride levels in adults with obese nutritional status.